Cholinergic Potentiation of Restoration of Visual Function after Optic Nerve Damage in Rats. (27th August 2017) - Chamoun, Mira; Sergeeva, Elena G.; Henrich-Noack, Petra; Jia, Shaobo; Grigartzik, Lisa; Ma, Jing; You, Qing; Huppé-Gourgues, Frédéric; Sabel, Bernhard A.; Vaucher, Elvire
Abstract : Enhancing cortical plasticity and brain connectivity may improve residual vision following a visual impairment. Since acetylcholine plays an important role in attention and neuronal plasticity, we explored whether potentiation of the cholinergic transmission has an effect on the visual function restoration. To this end, we evaluated for 4 weeks the effect of the acetylcholinesterase inhibitor donepezil on brightness discrimination, visually evoked potentials, and visual cortex reactivity after a bilateral and partial optic nerve crush in adult rats. Donepezil administration enhanced brightness discrimination capacity after optic nerve crush compared to nontreated animals. The visually evoked activation of the primary visual cortex was not restored, as measured by evoked potentials, but the cortical neuronal activity measured by thallium autometallography was not significantly affected four weeks after the optic nerve crush. Altogether, the results suggest a role of the cholinergic system in postlesion cortical plasticity. This finding agrees with the view that restoration of visual function may involve mechanisms beyond the area of primary damage and opens a new perspective for improving visual rehabilitation in humans.